2008
DOI: 10.1016/j.micromeso.2007.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of confinement in hybrid diamine-Rh complex-carbon catalysts used for hydrogenation reactions

Abstract: were characterized by X-ray photoelectron spectroscopy (XPS), X-ray absorption fine structure (XAFS), and inductively coupled plasma spectroscopy (ICP) for the determination of the metal content. The catalytic activity of the hybrid catalysts was tested in the hydrogenation of cyclohexene and carvone and it was found that they are more active than the homogeneous complex and reusable for at least 5 consecutive catalytic runs (with no leaching). Among the hybrid catalysts, those prepared with carbon nanotubes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Research has shown that metal particles (i.e., Ru, Co, and Fe) encapsulated inside CNTs exhibit superior catalytic performance compared with those loaded outside CNTs in hydrogenation [16], oxygen reduction [17], Fischer-Tropsch synthesis [18,19], and polymerization [20]. This superior catalytic performance can be attributed to the unique "confinement effect" of CNTs [21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that metal particles (i.e., Ru, Co, and Fe) encapsulated inside CNTs exhibit superior catalytic performance compared with those loaded outside CNTs in hydrogenation [16], oxygen reduction [17], Fischer-Tropsch synthesis [18,19], and polymerization [20]. This superior catalytic performance can be attributed to the unique "confinement effect" of CNTs [21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…The calculated F values give an indication of the location of the Rh species [24]. As a larger value of F corresponds to a more external location, the data indicate that the support properties M a n u s c r i p t 12 largely affect this aspect; the distribution of the Rh species is more homogeneous in carbon nanotubes than in carbon xerogels.…”
Section: Page 13 Of 24mentioning
confidence: 89%
“…The study of the surface chemistry was carried out by Temperature Programmed The rhodium content in the catalysts was determined after metal extraction and analysis of the solution by ICP-OES, using the methodology described in the literature [24]. The catalysts were also characterized by XPS employing a VG-Microtech Multilab 3000 spectrometer.…”
Section: Characterizationmentioning
confidence: 99%
“…As previously reported [26][27][28], the anchoring on the support is assumed to occur through a covalent siloxane-type bond created by reaction of methoxy functions with surface -OH type groups. It has been found that catalysts prepared in this way on different carbon materials are, in general, more active than the Rh(NN)Si in homogeneous phase and they are reusable [26][27][28]. Therefore, it was decided to extend the study to two structured carbon-based supports such as the CNF-monolith described above and a granular carbon xerogel.…”
Section: Introductionmentioning
confidence: 88%